2012
DOI: 10.1002/jcb.24170
|View full text |Cite
|
Sign up to set email alerts
|

A novel nuclear FGF Receptor‐1 partnership with retinoid and Nur receptors during developmental gene programming of embryonic stem cells

Abstract: FGF Receptor-1 (FGFR1), a membrane-targeted protein, is also involved in independent direct nuclear signaling. We show that nuclear accumulation of FGFR1 is a common response to retinoic acid (RA) in pluripotent embryonic stem cells (ESC) and neural progenitors and is both necessary and sufficient for neuronal-like differentiation and accompanying neuritic outgrowth. Dominant negative nuclear FGFR1, which lacks the tyrosine kinase domain, prevents RA-induced differentiation while full-length nuclear FGFR1 elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
111
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(121 citation statements)
references
References 64 publications
10
111
0
Order By: Relevance
“…MEME‐ChiP and other methods (Terranova et al, 2015) verified earlier findings (Lee et al, 2012) that nFGFR1 associates not only with the core AGGTCA sequences targeted by the classical nuclear receptors Nur77 and/or RXR, but also to sequences that are not targeted by Nur77 and/or RXT. nFGFR1‐targeted sites encompass the consensus sites for CREB, STAT, Sp1, and Smad as well other diverse TF that interact with CBP, and thus may engage in the nFGFR1‐CBP mediated transcriptional regulation.…”
Section: Binding Of Nfgfr1 Rxr and Nur77 And Gene Regulation (Terrasupporting
confidence: 81%
See 4 more Smart Citations
“…MEME‐ChiP and other methods (Terranova et al, 2015) verified earlier findings (Lee et al, 2012) that nFGFR1 associates not only with the core AGGTCA sequences targeted by the classical nuclear receptors Nur77 and/or RXR, but also to sequences that are not targeted by Nur77 and/or RXT. nFGFR1‐targeted sites encompass the consensus sites for CREB, STAT, Sp1, and Smad as well other diverse TF that interact with CBP, and thus may engage in the nFGFR1‐CBP mediated transcriptional regulation.…”
Section: Binding Of Nfgfr1 Rxr and Nur77 And Gene Regulation (Terrasupporting
confidence: 81%
“…Biophotonic assays, including FLIP and FRAP, have demonstrated that cytoplasmic FGFR1 exists in three separate populations: (1) an immobile, newly synthesized Endoplasmic Reticulum (ER) population; (2) a highly mobile, non‐glycosylated, cytosolic population; and (3) a slowly diffusing, membrane receptor population (Dunham‐Ems et al, 2006). Nuclear accumulation of FGFR1 in live cells is promoted by an accelerated cytoplasmic to nuclear import, as well by as a reduced nuclear to cytoplasmic export (Lee et al, 2012, 2013; Stachowiak et al, 2012b). In addition, activation of cell surface FGFR1 by FGF‐2 induces FGFR1 internalization, which is dependent upon the ARF6, Dynamin2 and Rab5 endocytic machinery, and is inhibited by cell surface E‐cadherin adhesion complexes (Bryant and Stow, 2005).…”
Section: Constitutive Plasma Membrane and Regulated Nuclear Targetingmentioning
confidence: 99%
See 3 more Smart Citations